Study on the soil pollution condition around the domestic wastewater - Jabbarov Zafarjon; Atoyeva Gulkhayo; Sayitov Sardor; Kurvantaev Rakhmon; Khakimova Nodira; Makhammadiev Samad; Kenjaev Yunus; Makhkamova Dilafruz; Jobborov Bakhrom; Nabiyeva Gulchekhra; Nurgaliev Najmiddin; Aliboyeva Malika; et al. (E3S Web of Conferences, 2024)
The rapid development in the population of the earth, the increase in the level of consumption of people leads to an increase in the amount of household waste from year to year, which, in turn, increases the negative impact on the environment of their collection and storage areas, that is, household waste landfills. From these studies, the state of contamination of the soil as scattered around the municipal landfill, the sources factors affecting the contamination were described. The main purpose of the conducted research is to determine the level of pollution of the soil under the influence of household waste. The researches were conducted in the soil scattered around the Tashkent municipal waste dump, located in the Ohangaron district were of the Tashkent province. The results showed that in the chemical pollution of irrigated typical gray soils, the domestic landfill is considered the main pollutant source, and the level of pollution decreases from the distance of 1.2 km from the landfill, and into according to the soil layers, it decreases uniformly from the top to the bottom, starting from the 70 cm layer.The soil scattered around the landfill is contaminated with organic pollutants, ash elements and heavy metals and other pollutants, including the total amount of Cd 3.1 times, As 4.39 times, Sb 2.46 times compared to the permissible limit share. , W 4.6 times and other heavy metals increased to different degrees.